Productive Zakat Empowerment by Baznas in Improvement of Mustahiq’s Economy in Kotamobagu - Edi Gunawan; Sahari Sahari; Deden Afandi; Wira Purwadi (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2021)
Zakat instrument plays an important role in religious scope. Zakat in Islamic principle, besides serving as a spiritually mandatory form of worship, can also be an alternativein poverty eradication process. Optimal zakat management and empowerment are needed for zakat to serve not only to perform worship spiritually but also as an instrument to eradicate poverty in the community, especially for Muslims. Improved understanding of the benefits of zakat both for muzzakiand mustahiqis very important. Zakat fund will not be spent only for consumption but can also be empowered for a productive business. Thus zakat is expected to change mustahiq’squality of life for betterment.